Teacher Preferences, Working Conditions, and Compensation Structure - Andrew C. Johnston (Institute of Labor Economics (IZA), 2020)
Improving schools depends on attracting high-caliber teachers and increasing retention, both made possible by appealing to teacher preferences. I deploy a discrete-choice experiment in a setting where teachers have reason to reveal their preferences. There are three main findings: (1) I calculate willingness-to-pay for a series of workplace attributes including salary structure, retirement benefits, performance pay, class size, and time-to-tenure. (2) Highly rated teachers have stronger preferences for schools offering performance pay, which may be used to differentially attract and retain them. (3) Under various criteria, schools seem to underpay in salary and performance pay while overpaying in retirement benefits.
Keywords: I20; J32; J45; M50; 330; teachers; labor market; achievement; retention; selection